POWER FLOW ANALYSIS CONSIDERING NEWTON RAPHSON, GAUSS SEIDEL AND FAST- DECOUPLED METHODS - Mohd Ghazali, Rohaizah; Sivalingam, Mathan; Zawawi, Siti Nor Baizura; Idris, Zahirrudin (Proceedings of the Informatics Conference, 2020)
Power flow analysis is a very important and fundamental tool for power system. Commercial power systems usually too complex for manual solution by hands. In addition, due to power flow equation which is nonlinear, more computation time were needed and become complicated as the number of bus increases in bus systems. This can be improvising by power flow solution iterative methods simulation. Iterative algorithm for solving power flow equations were simulated using MATLAB software. Objectives of the study are to obtain the power flow solution in distribution network which is the number of iteration required and system losses; to compare the power flow analysis with Newton Raphson (NR), Gauss Seidel (GS) and Fast Decoupled (FD) method. Three test system were discussed which are IEEE 9-bus system, IEEE 14-bus system, and IEEE 69-bus system and classified to three cases and were tested by three iterative algorithms proposed. Based on the results from three different cases, NR method required less number of iterations compared to FD and GS methods. Convergence by NR method is very fast and increases in number of bus system do not increase the number of iterations for NR. All three iterative algorithms successful to give the power flow solution forthree test case.